Dominant Factor of Household Food Security During COVID-19 Pandemic in Depok City in 2020 (Analysis of Secondary Data 2020) - Intan Hidayah (Universitas Airlangga, 2021)
Background: Food security is a condition when everybody has adequate physical and economical access to get nutritious and safe food to lead healthy and active life. COVID-19 pandemic can cause food security disruptions. This is because several people have lost their jobs and income so that they are no longer able to meet their food needs.